Downregulation of plasma insulin levels and hepatic PPAR expression during the first week of caloric restriction in mice - Mulligan, Jacob D. (2007)
Calorie restriction extends lifespan by decreasing the rate of tumor formation, an effect occurring within 8 weeks of initiating a restricted diet. Our goal was to define how the first weeks of a calorie restricted diet (60% of ad libitum calories) affects putative mediators of the calorie restriction phenotype, focusing on regulators of fatty acid biosynthesis. In C57Bl/6 mice, insulin decreased over 50% (p<0.05) during the first week of calorie restriction whereas IGF-1 was unaffected. In the liver, PPAR mRNA fell to 13% of baseline after one week of calorie restriction (p<0.05), whereas hepatic SREBP-1c and SIRT1 mRNA levels were unaffected. No changes in abdominal or subcutaneous adipose tissue were observed until after 8 weeks of caloric restriction. We conclude that calorie restriction-induced decreases in insulin and hepatic PPAR are rapid enough to support a role for these molecules in triggering the initial phase of the calorie restriction phenotype.